2011
DOI: 10.1051/0004-6361/201015731
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous formation of solar system giant planets

Abstract: Context. In the last few years, the so-called "Nice model" has become increasingly significant for studying the formation and evolution of the solar system. According to this model, the initial orbital configuration of the giant planets was much more compact than the one we observe today. Aims. We study the formation of the giant planets in connection with several parameters that describe the protoplanetary disk. We aim to establish which conditions enable their simultaneous formation in line with the initial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 59 publications
4
32
1
3
Order By: Relevance
“…This contraction triggers a very rapid accretion of gas, which is limited by the amount of gas that can be delivered by the protoplanetary disk surrounding the forming planet. This scenario has been studied by many authors, accounting for different physical effects, like protoplanet migration (Alibert et al 2004(Alibert et al , 2005, opacity reduction in the planetary envelope (e.g., Hubickyj et al 2005), excitation of accreted planetesimals by forming planets (e.g., Fortier et al 2007Fortier et al , 2013, competition between different planets (e.g., Guilera et al 2011). …”
Section: Dashed Lines Inmentioning
confidence: 99%
“…This contraction triggers a very rapid accretion of gas, which is limited by the amount of gas that can be delivered by the protoplanetary disk surrounding the forming planet. This scenario has been studied by many authors, accounting for different physical effects, like protoplanet migration (Alibert et al 2004(Alibert et al , 2005, opacity reduction in the planetary envelope (e.g., Hubickyj et al 2005), excitation of accreted planetesimals by forming planets (e.g., Fortier et al 2007Fortier et al , 2013, competition between different planets (e.g., Guilera et al 2011). …”
Section: Dashed Lines Inmentioning
confidence: 99%
“…Our model that describes the evolution of the protoplanetary disk is based on the works of Guilera et al (2010Guilera et al ( , 2011 with some minor improves incorporated. We used an axisymmetric protoplanetary disk characterized by a gaseous and a solid component.…”
Section: Improvements To Our Previous Modelmentioning
confidence: 99%
“…In previous works (Guilera et al 2010(Guilera et al , 2011 we developed a model for giant planet formation that calculates their formation Article published by EDP Sciences A96, page 1 of 14 immersed in a protoplanetary disk that evolves in time. In these previous works the population of planetesimals evolved by the accretion of the embryos and by planetesimal migration.…”
Section: Introductionmentioning
confidence: 99%
“…Thommes et al (2003), Chambers (2006), and Guilera et al (2010Guilera et al ( , 2011 showed that this effect has important consequences on the timescale of planetesimal accretion and in the planetesimal surface density evolution, especially for small bodies (r p 1 km). As a consequence of the conservation of mass, the planetesimal surface density obeys a continuity equation.…”
Section: Evolution Of Surface Densitiesmentioning
confidence: 99%